Emerging Chemical Agents for Microbiological Control of Tatsoi Sprouts - Aguayo, Encarna; Díaz-García, Rodrigo; Silveira, Ana Cecilia; Tarazona-Díaz, Martha Patricia; Escalona, Victor Hugo (Agrociencia Uruguay, 2012)
The fresh-cut industry shows a growing interest in fresh «baby» salads based on vegetable sprouts as Tatsoi. These vegetables should be disinfected using chemical and/or physical methods to maintain low microorganisms levels during their life. Nowadays, new chemical disinfectants substitutes to chlorine derivatives, more respectful of the environment and human health, are in study. In this work, the microbiological effectiveness of ascorbic acid (AA) at 30 and 60 mg L-1, chlorine dioxide (ClO2 ) at 7 and 10.5 mg L-1 were studied. As control sodium hypochlorite (NaClO) at 150 mg L-1 and water were used. The plant material was washed by immersion for two minutes in the disinfectant, rinsed with water one minute at 5 °C, centrifuged, and 30 g of sprouts were packed in trays that were stored at 5 °C for eight days. The lower counts of mesophilic (6.2 log cfu g-1), psychotrophics (4.8 log cfu g-1) and Enterobacteriaceae (3.5 log cfu g-1) were achieved using AA to 60 mg L-1. Yeasts had a lower growth than 3.4 log cfu g-1, using NaClO or ClO2 at 10.5 mg L-1. Therefore, AA and ClO2 , at concentrations of 60 and 10.5 mg L-1, behaved as good substitutes for NaOCl, capable of controlling microbial growth and maintain the life of Tatsoi sprouts at 5 °C for eight days without affecting sensory quality of the product.